Genetic and environmental variance components for physical activity patterns of twins. Exploring the possibilities of approximate entropy - Ramon de Brito Costa Pinheiro Lima; Rogério César Fermino; André Filipe Seabra; Rui Manuel Garganta; José António Ribeiro Maia (Universidade Federal de Santa Catarina, 2010)
The main objective of this study was to estimate the contribution of genetic factors to physical activity patterns (PAPs) in twins using approximate entropy (ApEn) statistics. The sample consisted of 162 monozygotic and dizygotic twins from Portugal aged 6 to 18 years. Physical activity was measured with a Tritrac-RT3 triaxial accelerometer over 5 days of a usual week. PAPs were described by ApEn using the Cine Wizard software. Zygosity was assessed by direct DNA analysis. Data were analyzed using the SYSTAT 10, STATA 10 and Twinan92 softwares. PAPs were estimated for 5, 3 and 2 days. In addition, structural equation modeling was used to compute different sources of variance genetic, common environmental and unique environmental variance. The level of significance was set at 5%. Sibling aggregation was identified by ApEn analysis, with monozygotic twins showing greater homogeneity. In conclusion, genetic factors accounted for 44 to 89% of the total variation in PAP.